1991
DOI: 10.1007/bf00002624
|View full text |Cite
|
Sign up to set email alerts
|

Chemical character and origin of organic acids in streams and seepage lakes of central Maine

Abstract: Abstract. Organic acids and inorganic chemistry were examined in seventeen seepage lakes, seven streams, and one seep in central Maine. The objectives of this analysis were to determine the quantity and quality of dissolved organic carbon (DOC), and to assess the relationship between organic and inorganic surface water chemistry. Lakes and streams sampled were dilute (average conductivity of 20.3 pScm-') with a wide range of DOC (125-2593 pmol C L-'). Organic acids in DOC were evaluated by:-DOC fractionation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 40 publications
(40 reference statements)
1
24
0
Order By: Relevance
“…Peterson (1990) suggested that a low color/DOC quotient also indicates poorly humified, less complex organic material from streams and lakes rather than from peatlands. In this same connection, David and Vance (1991) observed that those waters from streams and seepage lakes in Maine that were low in DOC also had small ratios of hydrophobic to hydrophilic acids. In those cases where DOC exceeded 10 mg L -~, the color/DOC quotients in Halifax County lakes sampled in December 1985 (Gorham et al 1986) were generally lower than those of the streams examined in December 1988, suggesting that colored organic matter in the lakes may have undergone relatively more breakdown than that in the streams, either photochemically or biochemically (Engstrom 1987).…”
Section: Stream Chemistrymentioning
confidence: 77%
“…Peterson (1990) suggested that a low color/DOC quotient also indicates poorly humified, less complex organic material from streams and lakes rather than from peatlands. In this same connection, David and Vance (1991) observed that those waters from streams and seepage lakes in Maine that were low in DOC also had small ratios of hydrophobic to hydrophilic acids. In those cases where DOC exceeded 10 mg L -~, the color/DOC quotients in Halifax County lakes sampled in December 1985 (Gorham et al 1986) were generally lower than those of the streams examined in December 1988, suggesting that colored organic matter in the lakes may have undergone relatively more breakdown than that in the streams, either photochemically or biochemically (Engstrom 1987).…”
Section: Stream Chemistrymentioning
confidence: 77%
“…This input of DOC was mainly in the form of hydrophobic acids, which have low charge density (Wellington and Driscoll, unpublished results). David and Vance (1991), in studying the origin of stream organic acids in Maine, found that DOC from wetlands and organic soil horizons had similar characteristics, both having high hydrophobic acid content and low charge density.…”
Section: Strong and Weak Organic Acid Anionsmentioning
confidence: 97%
“…McKnight et al, 1985;David and Vance, 1991). Organic acids are effective H ion buffers and can form complexes with inorganic Al.…”
Section: Inorganic and Organic Carbon In Soil Water And Surface Watermentioning
confidence: 99%